A review for chromium removal by carbon nanotubes. Issue 6 (3rd July 2017) - Anastopoulos, Ioannis; Anagnostopoulos, Vasileios A.; Bhatnagar, Amit; Mitropoulos, Athanasios C.; Kyzas, George Z.
ABSTRACT: Water pollution is still a serious problem for the entire world. Adsorption technology is a promising process which is based on the fabrication of novel, cheap, non-dangerous and highly sorptive materials for application in wastewater purification processes. Nanomaterials are functional groups which find use in many important fields such as medicine, food processing and agriculture. This review collects information from published works about the use of carbon nanotubes as efficient and promising adsorbents in chromium removal from (real or synthesised) wastewater. For this purpose, isotherm (Langmuir, Freundlich, etc.), kinetic (pseudo-first-, second-order, etc.), thermodynamic (free-energy Gibbs, enthalpy, entropy) and desorption–regeneration studies were discussed in detail. Moreover, significant factors such as pH, agitation time, temperature, adsorbent dosage and initial dye concentration are also reported extensively. The maximum monolayer adsorption capacities of Cr(III) and Cr(VI) ions were 0.39–238.09 and 1.26–370.3 mg/g, respectively. The absolute values of Δ G 0 and Δ H 0 ranged 0.237–48.62 and 0.16–58.43 kJ/mol, respectively.